Fear of Economic Cybercrime Across Europe: A Multilevel Application of Routine Activity Theory. (9th May 2022) - Cook, Steven; Giommoni, Luca; Trajtenberg Pareja, Nicolas; Levi, Michael; Williams, Matthew L
Abstract: Despite the increasing prevalence of cybercrime and its study by criminologists, very little research has examined the extent, nature, and impact of fear of cybercrime. In this study, we conducted a multilevel analysis of the 2018 Eurobarometer Cybersecurity Survey to test the applicability of routine activities theory on fear of economic cybercrime. We contribute to the literature by demonstrating that: (1) fear of economic cybercrime varies across EU member states; (2) country-level infrastructure development and income inequality are predictive of individual-level fear; (3) individual-level routine activities and sociodemographic variables are associated with fear; (4) country-level infrastructure development moderates the effects of individual-level guardianship. This paper concludes by emphasizing the importance of including country-level and individual-level determinants in fear of cybercrime research.